A study on public acceptance towards the implementation of GST in Malacca / Mohammad Afzanidzam Aziz - Aziz, Mohammad Afzanidzam (Faculty of Business and Management, 2016)
This paper is to examine public acceptance towards the implementation of GST in Malacca. However, there not much study about the public acceptance towards the implementation of GST in Malaysia or Malacca which mostly previous study is about public acceptance towards products or services. Thus, the theoretical framework was done. With a convenience sampling method used in this research, about 150 questionnaires distributed to the public before the results have revealed relationship and significant of conceptual framework of this topic. The researcher distributed the questionnaires among the public around Bandar Hilir on 16th November to 22nd November 2015. There are three conceptual factors which are knowledge, attitude and individual potential consumption behavior has been analysed. Then the result of the study would indicate the main influential public acceptance towards the implementation of GST in Malacca.